(untitled) (Journal of Psychiatrists’ Association of Nepal, 2019)
Introduction: Screening of mental disorders and psychological distress is important in clinical as well as research setting. The objective of this study is to test the reliability of mental health screening questionnaire developed by authors and see its correlation with perceived stress scale scores. Material and Method: A self-report screening instrument was designed by the authors in consultation with experts and was tested for reliability among 162 participants from general population gathered for stress management program. The correlation of the designed scale was tested with the Perceived Stress Scale score. Results: Scale reliability (Cronbach’s alpha) for the designed psychological distress scale was found to be 0.7558 which is regarded as having acceptable internal consistency. The questions of the designed scale had weak to moderate positive correlation with the score on Perceived Stress Scale. Conclusion: Despite many shortcomings of the designed scale we may be able to use it for basic screening of psychological distress and mental health problems. We recommend the validity of scale be tested in larger sample size.